Nutritional status of adult Tuberculosis patients in Burdwan municipality area of West Bengal - Mollah, Azharuddin; Shrivastava, Prabha; Das, Dilip Kumar; Ray, Soumalya (Indian Journal of Community Health, 2020)
Background: Nutritional status of a Tuberculosis (TB) patient plays a role in disease manifestation. Aims & Objective: To assess the nutritional status of adult tuberculosis patients under intensive phase of treatment. Settings and Design: A descriptive study with cross-sectional design was conducted at Burdwan Municipality of West Bengal. Methods and Material: In this study, TB patients aged 18 years and above receiving intensive phase of treatment, registered in the Tuberculosis units in the months of October-December, 2018 and residing in the municipality were approached. Nutritional status was evaluated through two approaches - dietary intake by twenty-four hours recall method and anthropometric status by measuring weight, height, BMI and MUAC. Data were analysed using SPSS v20. Results: Out of 113 study subjects, under-nutrition was present in 61.9% and inappropriate MUAC was observed in 68.1%. Interestingly, intake of Cereals and Millets among food groups was found to be deficient. The adjusted odds ratio for having under-nutrition among new cases compared to previously treated was 0.16 (0.33-0.82). Conclusions: For combating protein energy malnutrition in TB patients, emphasis should be given on balanced diet intake.